Cordycepin, lactoferrin, and Sargassum fusiforme polysaccharides protects against RSV via M2-like macrophage polarization - Fu, Xiaozong; Huang, Panwen; Zhang, Yuting; Li, Yanchang; Hu, Shichang (Frontiers in Immunology, 2025)
BackgroundRespiratory syncytial virus (RSV) is a leading cause of respiratory tract infections, particularly in infants and the older population, with limited effective treatments available. Cordycepin, lactoferrin, and Sargassum fusiforme polysaccharides (CLS) are natural compounds with antiviral and immunomodulatory properties. This study investigates the therapeutic potential of CLS in RSV infection.MethodsA murine model of RSV infection was used to evaluate the effects of CLS. Lung pathology was assessed by lung index, histology, and bronchoalveolar lavage fluid (BALF) albumin and LDH levels. Viral load was measured by RSV mRNA and protein expression. Alveolar macrophage depletion was achieved using clodronate liposomes, and macrophage polarization was analyzed via flow cytometry and RT-qPCR.ResultsCLS treatment improved lung pathology, reduced BALF injury markers, and decreased viral load. The therapeutic effects of CLS were abrogated by macrophage depletion, indicating a reliance on alveolar macrophages. CLS promoted M2-like macrophage polarization, increasing M2 markers and reducing M1 markers. In vitro, CLS reduced RSV-induced apoptosis and enhanced macrophage proliferation.ConclusionsCLS protects against RSV-induced lung injury by promoting M2-like macrophage polarization and reducing viral load. These findings support CLS as a potential therapeutic for RSV infections.